(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
Based on fragments of the crisis that has marked theatrical language over the last two centuries, this article aims to understand how approaches between theater and politics are reconfigured through the rhapsodic drive in the play The Story of Ronald, the McDonald’s Clown, by the playwright Spanish-Argentine Rodrigo García. It was possible to see that the work uses the juxtaposition and overflow of dramatic, lyrical and epic modes to compose a look that puts into tension the influence of large companies such as the American fast food chain on contemporary consumption. A dramaturgical language that reinvents paradigms and dialogues with the poetics of post-modernity.